1980
DOI: 10.1002/kin.550120906
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction Cl + HO2 = HCl + O2, using molecular modulation spectrometry

Abstract: The rate constant for the reaction (I), C1+ HOz -HCI + 0 2 , was measured using molecular modulation spectrometry to investigate HOz radical kinetics in the modulated photolysis of ClyH2-02 mixtures at 760 torr pressure. HOz was monitored directly in absorption at 220 nm, and k l was determined from computer simulations of the observed kinetic behavior of HOz, using a simple chemical model. The results gave kJk4 = 3.OtFh exp[+(2120 f 370)/T]where k s is the rate constant for the reaction of C1 with Hz. A conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 9 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…The potential importance of the Cl reaction with the HO 2 radical has led to a number of publications and, as a result, the kinetics of the HO 2 + Cl reaction have been studied experimentally for a range of temperatures. 8,[13][14][15][16] Lee et al 16 measured the rate constant of eqn (1) in a discharge-ow system with far infrared laser magnetic resonance within the temperature range 250-420 K. Similarly, Dobis et al 8 used mass spectrometry to measure the rate constant ((4.45 AE 0.06) Â 10 À11 cm 3 per molecule per s) of the reaction of eqn (1) in the temperature range 243-368 K. Both of these investigations showed that the rate constant in eqn (1) does not change within the measured temperature range. In another experiment, Hickson et al 9 used the discharge-ow resonance uorescence technique coupled with infrared diode laser spectroscopy to measure the rate constant for the reaction in eqn (1) within the temperature range 226-336 K. Their results show that the rate constant in eqn (1) derived from kinetic experiments expressed in Arrhenius form was (1.6 AE 0.2) Â 10 À11 exp[(249 AE 34)/T] cm 3 per molecule per s. The theoretical aspect of the kinetics and mechanism for the reaction of eqn (1) have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The potential importance of the Cl reaction with the HO 2 radical has led to a number of publications and, as a result, the kinetics of the HO 2 + Cl reaction have been studied experimentally for a range of temperatures. 8,[13][14][15][16] Lee et al 16 measured the rate constant of eqn (1) in a discharge-ow system with far infrared laser magnetic resonance within the temperature range 250-420 K. Similarly, Dobis et al 8 used mass spectrometry to measure the rate constant ((4.45 AE 0.06) Â 10 À11 cm 3 per molecule per s) of the reaction of eqn (1) in the temperature range 243-368 K. Both of these investigations showed that the rate constant in eqn (1) does not change within the measured temperature range. In another experiment, Hickson et al 9 used the discharge-ow resonance uorescence technique coupled with infrared diode laser spectroscopy to measure the rate constant for the reaction in eqn (1) within the temperature range 226-336 K. Their results show that the rate constant in eqn (1) derived from kinetic experiments expressed in Arrhenius form was (1.6 AE 0.2) Â 10 À11 exp[(249 AE 34)/T] cm 3 per molecule per s. The theoretical aspect of the kinetics and mechanism for the reaction of eqn (1) have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, an increase in the value of the factor from 4.1 × 10 13 to 4.1 × 10 15 resulted in a small increase in Hg conversion to 0.1%. As the rate of this reaction has been measured experimentally, 17,18 it is unclear whether such modifications can be justified.…”
Section: Simulations Of Experimental Data From Ghorishimentioning
confidence: 99%
“…These results are in good agreement with those obtained from HO 2 decay kinetics in excess of Cl. All the results for k 1 from the present work are shown in Figure 5 together with the data obtained in previous temperature-dependent studies of reaction (1) [5,8,9]. The continuous straight line in Figure 5, resulting from the least-squares analysis of the present data, provides the following Arrhenius expression: …”
mentioning
confidence: 90%